Fabrication and Characterization of High-Performance Crosslinked PVA/ PMDA Doped with H2SO4 - Abdulnabi, Rusul J.; Kareem, Aseel A. (Iraqi Journal of Science, 2022)
In the present study, pure Poly(viny1 alcohol) (PVA) and pyromellitic dianhydride (PMDA) cross linked PVA with (0,5,10,15 and 20)wt.% and doped with different molarity (5,9)M of sulfuric acid (H2SO4) were prepared by the solution casting method and were characterized as a function of frequency in the range (1-100) KHz. The FT-IR results showed that the strong broad band observed at 3738.05 and 3857.63 cm-1 may be assigned to O-H stretching due to the strong hydrogen bond of intramolecular and intermolecular type in PVA film. When PVA is doped with 5M and 9M H2SO4, a new peak was noticed at 813 cm-1, this peak may be due to the formation of hydrogen bond between the carbonyl (C=O) group of PVA and the H+ ion from the acid. As the PMDA concentration increases, the peak intensity of the O–H band 3738.05 cm−1 gradually decreases due to the reaction of more –OH groups of the PVA molecules with the –COOH group. Hence, it is difficult for the crosslinked PVA polymer chains to pack and form crystal regions, so the crosslinked PVA polymer chains become more flexible. The a.c. conductivity increases with the increase of frequency. FTIR spectra specified that the chemical reaction did occur between the PVA and the acid, therefore hydrogen ion (H+) can easily be separated from the carbonyl group and become free to move which explains proton conductivity of PVA. The increase of PMDA concentration has increased free volume and ionic mobility in the film with increasing cross-linkages. Dielectric constant decreases with increasing H2SO4 molarity for every frequency.